Crystal arthropathies. (February 2022) - Tan, Sean Y.W.; Stanway, James; Ellis, Spencer
Abstract: Crystal arthropathies are a diverse group of disorders characterized by deposition of various minerals in joints and soft tissues, leading to inflammation. Clinical presentations of the different types of crystal arthritis are often characteristic enough to differentiate them from each other and other inflammatory arthropathies; however, mistakes can be made, leading to delayed or incorrect management. Gout, the most common crystal arthropathy, is caused by monosodium urate crystal precipitation and appears to be increasing in clinical complexity and prevalence. Two other main crystal types are also associated with inflammatory symptoms resulting from crystal deposition in and around joints: calcium pyrophosphate dihydrate, causing pseudogout, and basic calcium phosphate (hydroxyapatite). The common forms of crystal-associated arthritis are most accurately diagnosed by identifying the specific crystals in synovial fluid. Crystal arthritis causes exquisite pain, and management is directed towards control of acute flares, followed by prevention of recurrent episodes, where possible. Traditionally – and still – gout prophylaxis has depended predominantly on allopurinol use, but other drugs such as febuxostat have proved useful for individuals who cannot tolerate allopurinol. Better understanding of the pathophysiology of the disorder has led to the development of biological treatments, which hold promise for resistant cases and severe disease.